2016
DOI: 10.4238/gmr.15017510
|View full text |Cite
|
Sign up to set email alerts
|

Association between ERCC5 gene polymorphisms and gastric cancer risk in a Chinese population

Abstract: ABSTRACT. We conducted a hospital-based case-control study to investigate the association between 3 common SNPs in the ERCC5 gene (rs1047768, rs751402, and rs17655) and the risk of developing gastric cancer. Between January 2013 and December 2014, samples were collected from 216 gastric cancer patients and 216 control subjects. ERCC5 rs1047768, rs751402, and rs17655 polymorphisms were genotyped by polymerase chain reaction combined with restriction fragment length polymorphism analysis. By conditional logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The final meta-analysis included 47 articles. There were 22 articles with 12,833 cases and 151,86 controls for rs1047768 T>C [ 7 9 , 12 , 14 31 ], 14 studies with 11,327 cases and 12,684 controls for rs2296147 T>C [ 9 11 , 13 , 18 , 24 , 26 28 , 32 – 37 ], 11 studies with 5,898 cases and 7,448 controls for rs2227869 G>C [ 8 , 9 , 14 , 17 , 18 , 20 , 22 , 25 , 38 40 ], 17 studies with 9,826 cases and 10,552 controls for rs2094258 C>T [ 10 , 11 , 18 , 24 , 26 28 , 34 – 37 , 41 – 46 ], 21 studies with 10,369 cases and 11,207 controls for rs751402 C>T [ 10 , 13 , 24 , 26 29 , 31 , 32 , 36 , 37 , 42 45 , 47 52 ], and 14 studies with 10,873 cases and 12,535 controls for rs873601 G>A [ 9 11 , 18 , 24 , 26 28 , 32 , 34 , 36 , 52 54 ]. A flow chart summarizing the process of relevant study identification is shown in Figure 1 , and the study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The final meta-analysis included 47 articles. There were 22 articles with 12,833 cases and 151,86 controls for rs1047768 T>C [ 7 9 , 12 , 14 31 ], 14 studies with 11,327 cases and 12,684 controls for rs2296147 T>C [ 9 11 , 13 , 18 , 24 , 26 28 , 32 – 37 ], 11 studies with 5,898 cases and 7,448 controls for rs2227869 G>C [ 8 , 9 , 14 , 17 , 18 , 20 , 22 , 25 , 38 40 ], 17 studies with 9,826 cases and 10,552 controls for rs2094258 C>T [ 10 , 11 , 18 , 24 , 26 28 , 34 – 37 , 41 – 46 ], 21 studies with 10,369 cases and 11,207 controls for rs751402 C>T [ 10 , 13 , 24 , 26 29 , 31 , 32 , 36 , 37 , 42 45 , 47 52 ], and 14 studies with 10,873 cases and 12,535 controls for rs873601 G>A [ 9 11 , 18 , 24 , 26 28 , 32 , 34 , 36 , 52 54 ]. A flow chart summarizing the process of relevant study identification is shown in Figure 1 , and the study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the results from basic medical research need to be confirmed by population studies. In recent years, some articles (13)(14)(15)(16)(17)(18)(19)(20)(21) have investigated the correlation between rs751402 mutation and GC risk among populations, but the results have been controversial. A possible explanation is that most of these studies have had small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Since transcription of XPG is correlated with altered transcription domain-associated repair capacity (12), this promoter mutation seems to be associated with cancer. Studies have estimated the association between XPG genetic polymorphism (rs751402 C>T) and risk of GC (13)(14)(15)(16)(17)(18)(19)(20)(21). However, their conclusions remain conflicting.…”
mentioning
confidence: 99%